Preparation of Photocatalytic TiO2-Polyacrylonitrile Nanofibers for Filtration of Airborne Microorganisms - Bahman Pourhassan; Farideh Golbabaei; Somayeh Farhang Dehghan; Mohammad Reza Pourmand; Tahereh Mousavi; Ensieh Masoorian (Tehran University of Medical Sciences, 2022)
Background: We aimed to investigate the efficiency of neat polyacrylonitrile (PAN) nanofibers and photocatalytic PAN/TiO2 nanofibers for removal of airborne microorganisms. Methods: Nanofibers were fabricated from 16 wt% of PAN dissolved in dimethyl formamide through the electrospinning technique. The efficiency of media for removal of Staphylococcus epidermidis and Bacillus subtilis was investigated at different conditions such as face velocity, relative humidity, air temperature and UVC radiation intensity. as face velocity (0.1 and 0.3 m/s), relative humidity (35±5% and 60±5%), air temperature (22±3 °C and 30±3 °C) and the UVC radiation intensity (dark, 1±0.09 mW/cm2 and 1.8±0.07 mW/cm2) using air sampling from upstream and downstream of media by cascade impactor containing blood agar culture medium. Results: The mean diameter of electrospun fibers and coefficient of variation were 194 nm and 15%, respectively. The amount of immobilized TiO2 on the filter was 620±6.56 mg/m2. Photocatalytic nanofiber filter media presented the best performance for removal of airborne B. subtilis at 60±5% relative humidity, 0.1 m/s face velocity, air temperature 22 °C, and 1.8 ± 0.07 mW/cm2 UVC radiation. Conclusion: The filtration efficiency of photocatalytic media was significantly higher than neat ones. Lower efficiency of media was found in the higher air velocity for all bioaerosols. High UVC radiation intensity increased filtration efficiency. Moreover, the increase in air temperature and relative humidity (except for TiO2-coated media under UVC radiation) did not significantly affect the filtration efficiency of all media.